CAREGIVERS BURDEN AND TREATMENT SEEKING BEHAVIOR AMONG NEUROTIC AND PSYCHOTIC PATIENTS: A CROSS- SECTIONAL STUDY - Hira Kiani,; Sharafat Ali; Abdur Rahman; Alam Zeb Khattak; Sadaf Fardoos (Al-Qanṭara, 2023)
This study aims to recognize relationship of caregivers’ burden and treatment seeking behavior among neurotic and psychotic patients in Rawalpindi Islamabad. A total of 100 Caregivers of patients fulfilling the diagnostic criteria of Diagnostic and Statistical Manual for Mental Disorders-04 or International Classification of Diseases-10 for psychotic and neurotic disorders from different clinics, hospitals. They were assessed through Zarit Burden Interview Scale (CBI) and Attitude towards psychological help seeking scale (ATPPHS). 50% caregivers were females and 50% males. 26% of caregivers belonged to the rural areas followed by 31% belonging to the urban areas. 34%of caregivers who had time spend from less than three years and 23% of caregivers who had time spend from more than three years while providing care. Whereas 37% of caregivers belonged to persons suffering from neurotic disorders and 24% of caregivers belonging to a person’s suffering from psychotic disorders. 16% opted traditional approaches, 36 % sought general medical and 42% opted psychological treatment services. Association found between caregivers’ burden and treatment seeking behavior among neurotic and psychotic patients and there is also an association of demographic factors with caregivers’ burden and treatment seeking behavior. It is concluded that the social support of the family, friends and others decreases the level of burden while suffering a caring process among the caregivers of neurotic and psychotic patients. It is also concluded that psychological educational programs through psychiatric institutions community mental health services pointing family members helps to understand signs and symptoms of the patient’s disorder, groups of treatment and significance of psychosocial support. Keywords: caregivers, caregivers’ burden, treatment seeking behavior, neurotic patients, psychotic patients.